The nigerian financial superstructure, financial intermediation, and environmental factors: issues, empirical evidence, and managerial implications - Ezirim, Chinedu B; Muoghalu, Michael I; Emenyonu, Emmanuel (Journal of African Business, 2004)
The paper empirically investigates the extent to which environmental factors affect the intermediation performance of the financial superstructure in Nigeria. A number of intermediation-environmental models were constructed and estimated against annual Nigerian data from 1970 to 2000. Among the various environments of financial intermediation, the socio-political environment, the regulatory environment, and the eco-financial environment exert very great influences on the operations of the financial superstructure. This is based on the evidence from the results, which revealed the socio-political index, regulatory index, and foreign exchange market variables as the most critical predictors of the financial intermediation-output-related index. Other factors such as inflation, taxation, financial market imperfection, and the growth rate of the economy appear not to exert statistically significant effects on the intermediation operations of the financial superstructure. Generally, the utility of the specified models was satisfied as indicated by the results of the global statistics. © 2004 by The Haworth Press, Inc. All rigths reserved.
Keywords: Africa; Eastern Hemisphere; Environmental factors; Financial institutions; Financial intermediation; Financial markets; Financial superstructure; Financial system; Nigeria; Sub-Saharan Africa; West Africa; World; dept.acc; growth rate; management practice; market conditions; performance assessment